Trends In Acoustic Neuroma Management: A 20-Year Review of the Oxford Skull Base Clinic - MacKeith, Samuel A. C.; Kerr, Richard S.; Milford, Chris A. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To describe the change in the management of acoustic neuromas at one United Kingdom center over a 20-year period and to compare this with what is known regarding trends in practice on a national and international scale.Design, Setting, and Participants Data was collected prospectively on all patients attending the Oxford Skull Base Clinic between 1990 and 2009.Main Outcome Measures The proportion of patients managed initially by observation versus radiotherapy versus surgery was recorded for each year.Results Significantly more patients received radiation treatment (instead of surgery) between 2000 and 2009 when compared with 1990 to 1999. Compared with national audit data, the Oxford Skull Base Clinic treats a higher proportion of patients with radiotherapy and significantly lower proportion with surgery, though the trend nationally is toward more observation and radiotherapy and less surgery.Conclusion Surgery will remain crucial in the management of some patients with acoustic neuromas (usually those with the larger tumors where radiosurgery is recognized to be less appropriate), but using current trends to predict future practice would suggest that alternative nonmicrosurgical treatment may play an increasingly important role in the future.
Keywords: acoustic neuroma; management; trend; radiosurgery; vestibular schwannoma